20-3(7-6P)+9P=

Simple and best practice solution for 20-3(7-6P)+9P= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20-3(7-6P)+9P= equation:


Simplifying
20 + -3(7 + -6P) + 9P = 0
20 + (7 * -3 + -6P * -3) + 9P = 0
20 + (-21 + 18P) + 9P = 0

Combine like terms: 20 + -21 = -1
-1 + 18P + 9P = 0

Combine like terms: 18P + 9P = 27P
-1 + 27P = 0

Solving
-1 + 27P = 0

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 27P = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 27P = 0 + 1
27P = 0 + 1

Combine like terms: 0 + 1 = 1
27P = 1

Divide each side by '27'.
P = 0.03703703704

Simplifying
P = 0.03703703704

See similar equations:

| 2x+24x=180 | | 5(1.3-6.5x)-6(8.1x-4)=7.1x-12.3 | | 5-7x=45-14x | | 5x-4-6x=-10 | | 0.25(8k-4)=k+8-2k | | 8.1a+2.3=5.1a | | 30x+20=30 | | -1.20a=8 | | 8p-2=3p+6 | | -1.2a=8 | | 4x+7=25-2x | | (4x+2)-2(x+1)=12 | | b+6b=-16+3b | | -7+4x=-35 | | 0.72x-19.7=0.3(.2x+18) | | -2x+15=-35 | | -x+1+2x=2 | | 75.00+25x=162.5 | | 3x+27=54 | | 13d-25=3d | | -2c=-16 | | 2x-7=25-2x | | 8ln(11-6x)=4 | | 5x-9-x=7 | | x+5=9x-3 | | xa^2=c-b | | 5x-4+2x=2x+1 | | 6m+16=45x+18-13 | | 1.5h-5=1 | | 4x+31=12x-39 | | ax^2=c-b | | n-n-12=0 |

Equations solver categories